Pharmacodynamics for Nursing Students - Lim, William/W.K. (YouTube, 2020)
A video primer on pharmacodynamics to introduce nursing students to the receptor theory for drug action, the difference between potency and efficacy, and how drugs are classified as agonists (full or partial) or antagonists (reversible or irreversible).